Modificação química da casca do coco bruto (Cocos Nucifera) para remoção de Cu(II) de efluente sintético e industrial: estudo de isoterma de adsorção, cinética e coluna de leito fixo - Sousa Neto, Vicente de Oliveira (2012)
The heavy metals are known to be highly toxic at very low concentrations in water. At this point, numerous studies have been dedicated to their removal to acceptable limits of an environmental point of view. Such researches are focused mainly in developing an efficient removal and low cost. Many methods have been proposed for removing heavy metals, for example, precipitation, membrane filtration, ion exchange and adsorption. The precipitation is one method that has been used more although an inappropriate method regarding the environmental impact for generating residues. The bagasse, coconut offers natural facility to be found and handled, so it is one of the most studied materials for reuse. This paper aims to make a study of adsorption of Cu 2+ using bagasse as adsorbent modified coconut. The modifications were employed (a) by polymerization of formaldehyde in sulfuric acid medium, b) treatment with ionic líguido c) Esterification acid and multicarboxílicos multifenólicos. The models applied to the study of isotherms were Langmuir, Freundlich, Temkin and Dubinin-Raduschevich. Applying the model in the study of Langmuir Adsorption of Cu (II) adsorbent modified BCFB the maximum adsorption capacity qm and kL were contained 125 mg.g-1 and 1.11 x10-2L.mg for Cu +2. For adsorbentes BC / LI and BCTânico the qm value were 64.5 and 99mg.g-1 respectively as kL value were 5.3 x10-2 5.6 x10-2 respectively. The kinetic model that best fit the phenomenon was the second order. The results showed that the coconut coir chemically modified is a potential adsorbent for removing Cu2+. The study column was used to verify the performace of the adsorbent when employing industrial effluent. Under the conditions employed in this study was modified with tannic acid that had shown the best removal performance desempenho removal. Also the reusability of the adsorbent is remarkable since it promotes a lowering cost, considering its applicability on an industrial scale.